David and Goliath - Mayo, Diana (New York : F. Watts, 2000)
Retells the Bible story of the battle between the boy David, armed with only a sling, and the giant warrior Goliath
Keywords: David, -- King of Israel -- Juvenile literature; Goliath -- (Biblical giant) -- Juvenile literature; David, -- King of Israel; Goliath -- (Biblical giant); Bible stories -- O.T